Upaya Meningkatkan Kemampuan Kognitif dalam Mengenal Bentuk- Bentuk Geometri melalui Permainan Dakon Geometri pada Anak Usia Dini Kelompok B: Penelitian - Perpetua Welerubun; Minuk Riyana; Muh. Rafi’y (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to see the increase in cognitive abilities in recognizing geometric shapes through the geometric Dakon game in early childhood group B at St. Mary’s Kindergarten Bernadetha. This research is descriptive qualitative research using the Classroom Action Research (PTK) method, which was carried out in one cycle of two meetings. Classroom action research is designed through planning, implementation, observation, and reflection. The tools used in collecting data are student observation sheets, student worksheets, student activity sheets, and documentation results. The research subjects were children from group B class of St. Mark, totaling 16 children.The results of the research show that children's ability to recognize geometric shapes has a fairly good percentage. Before the action was carried out, the child's understanding of geometric shapes was still 0%. However, children's understanding experienced an increase seen in the first cycle of action at meeting I by 68.5% and increased to 81.25% at meeting II. The indicator for achieving success is at least 75% in the very good category.